POTENSI INTERAKSI OBAT JANTUNG DI SALAH SATU APOTEK KARAWANG - Lina Aliyani Mardiana (Jurnal Buana Farma, 2022)
Cardiovascular disease is a group of diseases of the heart and blood vessels which includes: coronary heart disease, cerebrovascular disease, peripheral arterial disease, rheumatic heart disease, heart disease congenital heart disease, deep vein thrombosis and pulmonary embolism. Drug interactions are one of the factors that affect the body's response to treatment and are considered clinically important if they cause poisoning and/or reduce the effectiveness of the interacting drug resulting in a change in the therapeutic effect. Pharmacies are places for selling and buying licensed drugs, and there must be APA that has obtained a permit, as well as assistant pharmacists who have received SK, and pharmacist assistants who have graduated from a pharmacy degree. Clinical pharmacy services are direct services provided by pharmacists to patients in order to improve therapeutic outcomes and minimize the risk of side effects that may occur. includes assessment and prescription services, drug information services (PIO), home care, drug therapy monitoring (PTO), drug side effects monitoring (MESO), and counseling including for self-medication and recording of drugs used in PMR (patient medication record).